Eczema-like Eruption Limited to the Right Sole: Localised Scabies - Ömer Faruk Elmas; Muttalip Çiçek (Türkiye Parazitoloji Dergisi, 2020)

(untitled)
Scabies is a cutaneous infectious disease caused by the ectoparasite Sarcoptes scabiei. The disease has gained attention due to its increasing incidence in recent years. Rare and atypical forms of scabies can imitate many other cutaneous conditions. Such unfamiliar presentations may lead to misdiagnosis and mistreatment. Localised scabies is extremely rare and only few cases have been reported in the relevant literature. Herein, we report the case of a 4-month-old girl presenting with localised scabies limited to the right plantar surface. To the best of our knowledge, scabies restricted to the plantar region has never been reported in the paediatric population. Furthermore, scabies restricted to a single foot has never been reported in any age group. Awareness about the atypical and extraordinary manifestations of scabies can lead to early diagnosis and treatment and, thus, decrease diseaserelated morbidity and risk of transmission.